(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
Among the documents recording horse inventories of the Commune of Perugia between 1276 and 1292, there is a vast compendium of magagnae—diseases mostly designated by terms unknown to medieval Latin and of obscure meaning, suggesting a clinical vocabulary of veterinary pathologies. Cross-referencing these with the principal equine veterinary treatises circulating at the time confirms this interpretation, offering rare evidence of the actual application of what can be seen, beyond the written page of the treatises, as a genuine proto-veterinary medical science. Indeed, it is exactly from the mid-13th century onward, beginning with De medicina equorum by Giordano Ruffo, that veterinary medicine underwent a renewal marked by a practical and empirical character—a turning point from earlier traditions and classical auctoritates, which were characterized by a predominantly theoretical knowledge that had seemingly become, at least in part, obsolete. By using these two diverse types of primary sources—on one hand, the administrative records of a 13th-century commune, and on the other, the key treatises composed and circulating at the time—it becomes possible to enrich the narrative scope of both. What emerges is a deeper understanding of how veterinary knowledge was compiled and transmitted, as well as insights into the professional and para-educational dimension of mascalcia, a trade of considerable cultural significance in the society of the time.